Chapter I: Survey of the Problem (Quarterly Journal of Economics, 1941)
Chapter I: Survey of the Problem The Quarterly Journal of Economics, Volume 56, Issue 1_Part_2, November 1941, Pages 1–32, https://doi.org/10.1093/qje/56.1_Part_2.1 Published: 01 November 1941